THE RELEVANCE OF ENTREPRENEURIAL EDUCATION TO STUDENTS INTENTION OF BUSINESS INTEREST - Ridwan Idris; Lisa Nursita (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
This article examines the relevance of entrepreneurial education at Islamic State University Alauddin Makassar, which organize to encourage the student's intention of business interests. This article applied a combination method of multiple linear regression analysis and scale ranges based on Likert Scale instruments. The sampling method is cluster sampling, with the population coming from students spread across various faculties at Islamic State University Alauddin Makassar. The study results showed that their entrepreneurial interest intentions were significantly and positively influenced by their knowledge level about entrepreneurship and the learning process that applied entrepreneurial practices. However, the student’s definition of entrepreneurship interest at Islamic State University Alauddin Makassar is still in the moderate category. It is influenced by the not optimal application of the entrepreneurial project-based learning process, which was carried out by all lecturers who gave lectures on entrepreneurship courses that caused the students not to get the entrepreneurship experience in their learning process. On the other hand, the learning process with project-based learning media provides a direct experience to students who can help the graduates' rates. Therefore, higher education should be able to create an ecosystem that can motivate the development of business actors among students.